2019
DOI: 10.1097/sla.0000000000003224
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 1116 Consecutive Patients Diagnosed With Anterior Cutaneous Nerve Entrapment Syndrome (ACNES)

Abstract: Objective: The aim of this study was to discuss patient history and subjective findings at physical examination in a large case series to validate a proposed comprehensive set of major and minor diagnostic criteria. Summary Background Data: Chronic abdominal pain in some patients is caused by the anterior cutaneous nerve entrapment syndrome (ACNES). ACNES is a clinical diagnosis as no functional testing or imaging modalities are available up to date. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 14 publications
3
47
0
9
Order By: Relevance
“…Although previous literature has indicated up to 42% of patients having complete pain remission after injection of local anesthetic into the abdominal wall alone, patients with persistent pain are forced to search for alternative methods of pain relief. 9,10 The addition of adjuvants to local anesthetic has been attempted for longer duration of pain relief. One such adjuvant, dexamethasone, has been shown to prolong the effect of long-acting anesthetics up to 1,306 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous literature has indicated up to 42% of patients having complete pain remission after injection of local anesthetic into the abdominal wall alone, patients with persistent pain are forced to search for alternative methods of pain relief. 9,10 The addition of adjuvants to local anesthetic has been attempted for longer duration of pain relief. One such adjuvant, dexamethasone, has been shown to prolong the effect of long-acting anesthetics up to 1,306 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent retrospective studies have shown that pseudovisceral symptoms, including a change in defecation habits, appetite suppression, nausea, and bloating can be associated with ACNES. 8 Current treatment options include pharmacologic therapy, trigger point injections, ultrasound-guided nerve blocks, chemical neurolysis, and surgical neurectomy. 5 We present a case of a 50-year-old female with chronic abdominal pain who was diagnosed with ACNES.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 1,116 patients by Mol et al [7], ACNES was 3.7 times more common in females. While the median age was 42 years, ACNES has been reported in children as well as octogenarians.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of ACNES in our patient also presented a challenge. While more than half of ACNES cases arise spontaneously, other known triggers include recent abdominal surgery, abdominal trauma, exercise, pregnancy, and influenza [7]. A case of ACNES thought to be triggered by oral contraceptives has also been reported [14].…”
Section: Discussionmentioning
confidence: 99%
“…Als de pijnklachten terugkwamen, werd opnieuw een injectie geplaatst met 2-5 ml lidocaïne waaraan 40 mg methylprednison was toegevoegd. Toevoegen van een corticosteroïd is bij ACNES overigens niet zinvol gebleken: die toevoeging bleek in een recente studie naar de effectiviteit daarvan niet te leiden tot een verschil met het injecteren van lidocaïne alleen [10].…”
Section: Interventieunclassified